Porous Liquids Responsive to Light - Dinker, Manish Kumar; Zhao, Kan; Dai, Zhengxing; Ding, Lifeng; Liu, Xiao‐Qin; Sun, Lin‐Bing (Angewandte Chemie International Edition, 2022)
A porous liquid is a unique liquid medium that combines the cavity of porous solids with the fluidity of liquids. This special characteristic offers potential in various applications. Here we report a type II photoresponsive porous ionic liquid (PPIL) from dissolving a photoresponsive metal‐organic polyhedron (PMOP, constructed from dicopper and azobenzene‐containing carboxylate) in a polyethylene‐glycol‐functionalized bulky ionic liquid (IL). Owing to favorable ion interactions, bulky IL molecules encircle outside PMOP, and the inter cavities are maintained. The azobenzene moieties can be isomerized freely in the PPILs to expose and shelter active sites upon visible and UV light irradiation. Hence, the adsorption capacity of PPILs is controllable by light irradiation, and the change in CO2 uptake is up to 30 % compared to neat IL. This study may inspire the development of new adsorption process regulated by light instead of pressure and temperature swing adsorption. A type II photoresponsive porous ionic liquid (PPIL) with permanent cavities is formed by dissolving Cu‐based metal‐organic polyhedron (MOP) in bulky ionic liquid .The MOP carries azobenzene moieties as pendant groups which undergo trans‐ and cis‐isomerization under visible and UV light irradiation and thus, a controlled CO2 uptake and release is realized.